The effect of TQM, leadership and innovation on organizational performance of Dubai Police: the mediating role of organizational culture - Eshaq, Muneer Dhaif Allah Saeed (2022)
This study aimed to investigate the direct impact of total quality management (TQM), leadership, innovation, and organizational culture on the organizational performance of the Dubai police, and the mediating role of organizational culture. A quantitative research approach was employed. Data were collected using questionnaires from a sample of 314 Dubai Police officers, which were selected using the cluster random sampling technique. The preliminary analysis and descriptive statistics were run using SPSS version 25 while hypotheses were tested using the structural equation modelling via Smart PLS version 3. For the direct path analysis, the findings revealed a direct relationship between TQM and organizational performance (=0.662, t=11.583, p<0.05), innovation and organizational performance (=0.109, t=2.374, p<0.05), TQM and organizational culture (=0.490, t=9.115, p<0.05), innovation and organizational culture (=0.347, t=6.080, p<0.05), and organizational culture and organizational performance (=0.131, t=2.022, p<0.05). Leadership, on the other hand, does not impact organizational performance (=0.036, t=1.114, p>0.05). The findings also indicated that organizational culture significantly mediates the relationship between TQM and organizational performance (=0.064, t=1.975, p<0.05), as well as the relationship between innovation and organizational performance (=-0.045, t=2.012, p<0.05). The findings also revealed organizational culture as an insignificant mediator in the relationship between leadership and organizational performance (=-0.001, t=0.131, p>0.05). In conclusion, TQM and innovation play a significant role to boost organizational culture and organizational performance, and organizational culture could mediate the effect of TQM and innovation on organizational performance. In implication, the findings provide useful guidance for managers, field practitioners, and decision-makers to design programs to strengthen their organisations' performance, particularly by highlighting the significant roles of TQM, innovation, and organizational culture, as well as presenting an enhanced model to be adopted by public or private organizations in the UAE, particularly the Dubai police departments.